Moisture Susceptibility of Hot Mix Asphalt Mixtures Modified by Nano Silica and Subjected to Aging Process (Journal of Engineering, 2023)
Moisture damage is described as a reduction in stiffness and strength durability in asphalt mixtures due to moisture. This study investigated the influence of adding nano silica (NS) to the Asphalt on the moisture susceptibility of hot-mix-asphalt (HMA) mixtures under different aging conditions. NS was mixed with asphalt binder at concentrations of 2%, 4%, and 6% by weight of the binder. To detect the microstructure changes of modified Asphalt and estimate the dispersion of NS within the Asphalt, the field emission scanning electron microscope (FE-SEM) was used. To examine the performance of Asphalt mixed with NS at different aging stages (short-term and long-term aging), asphalt mixture tests such as Marshall stability, flow, and Tensile Strength Ratio Test (TSR) were performed. According to the FESEM images, the NS particles in the mixture were sufficiently dispersed. The findings demonstrate that the NS enhances pavement performance by enhancing stability and volumetric characteristics and reducing susceptibility to moisture damage.  Furthermore, TSR values of aged specimens show that increasing the NS content significantly reduces susceptibility to moisture and oxidative aging.